Comprehensive assessment of adverse event profiles associated with bispecific antibodies in multiple myeloma - Golmohammadi, Mobina (My University, 2025)
Background: Multiple myeloma (MM) represents a hematological malignancy characterized by the uncontrolled proliferation of malignant plasma cells within the bone marrow. Ongoing research endeavors are focused on investigating the potential of Bispecific T Cell engagers (BiTEs) as a therapeutic approach for relapsed/refractory MM, demonstrating promising preliminary results. Methods: We conducted a comprehensive review of the available biomedical literature, including abstracts and full publications, using PubMed, Scopus, and Nature databases until the beginning of 2023. BiTEs were classified into two groups: B-cell maturation antigen (BCMA) and nonBCMA targeting BiTEs, which included GPRC5D, and GPRC5DxBCMA. Our study included 23 different trials. Data about the frequencies of various adverse events (AEs) including hematological and non-BCMA hematological were collected. A pooled analysis based on Welch's t-test was then performed on all BiTEs to compare the safety profile of each agent from BCMA and non-BCMA. For clustering, we used t-distributed stochastic neighbor embedding (t-SNE). Results: In this research, we looked at various studies involving a total of 1,899 patients with MM across twenty-three trials. Among them, 1,094 patients received treatment with BCMA inhibitors, while 677 patients were treated with non-BCMA inhibitors. Additionally, 65 patients were treated with a combination of Teclistamab and Talquetamab (Tec_Tal), and 63 patients received a combination of Talquetamab and Daratumumab (Tec_Dar). The median follow-up for all groups was 12.6 months. In terms of all-grade hematological AEs, neutropenia was observed in 43.87% of patients, anemia was observed in 43.96%, infections occurred in 44.05%, CRS was reported in 64.16%, and lymphopenia was observed in 40.33%. For grade 3/4 AEs, the percentages were as follows: neutropenia 40.03%, infections 18.18%, CRS 1.84%, anemia 28.48%, and lymphopenia 45.09%. Upon conducting a comprehensive pooled analysis, subtle disparities emerged between BCMA and non-BCMA BiTEs. More instances of CRS and CRS with Tocilizumab occurred with BCMA BiTEs vs non-BCMA BiTEs, P<0.024. Friedman's findings emphasized substantial distinctions between BCMA and non-BCMA agents for both overall and severe grade 3/4 AEs (p<0.0001). t-SNE was applied to examine the clustering patterns among agents across all grades and grade 3/4 AEs. The findings revealed that agents with all grades and grade 3/4 showed similar clustering patterns except for two agents. Conclusion: The use of BiTEs in MM has demonstrated efficacy; however, these have been linked to a unique AE profile. Our results showed that non-BCMA were associated with less hematotoxicity (combined grade 3/4 AEs and hypogammaglobulinemia), whereas BCMA BiTEs were associated with less CRS rates. This is important information for treatment selection and mitigation strategy development aiming to optimize patient outcomes.
Keywords: BCMA; Pooled analysis; Clustering